Cavalos grandes e pequenos - Santos, Lucimar Moraes dos; Pereira, Gecimar Alves; Fernandes, Jose Fausto; Bordinhão, Andréia Jonceline Chiozini; Simião, Regina Aparecida Versoza (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2021)
>>> ver pdf